ARKEOASTRONOMI MASYARAKAT NELAYAN KABUPATEN KEPULAUAN SELAYAR DALAM MENENTUKAN CUACA PERSFEKTIF ILMU FALAK: ARKEOASTRONOMI MASYARAKAT NELAYAN KABUPATEN KEPULAUAN SELAYAR DALAM MENENTUKAN CUACA PERSFEKTIF ILMU FALAK - Satria; Kiljamiawati; Aisyah, Nur (HISABUNA: Jurnal Ilmu Falak, 2024)
When doing their vocation as fisherman, the Selayar Islands Regency's fishing community draws on their predecessors' heritage. To decide whether to go to work or not, people look to natural occurrences such as the moon, constellations, the direction of the weather, and the cardinal directions. In fact, technology has advanced quickly in comparison to today, making it simpler for people to meet their needs, including assessing the weather and cardinal directions. This kind of study uses a qualitative field research methodology. The interview method (interview) and documentation method (documentation) are both used to acquire data. The data is descriptively evaluated, describing how constellations are used or utilized as natural occurrences. in the Selayar Islands Regency by fisherman, as well as the moon. This study examines how the fishing industry in the Selayar Islands Regency makes use of natural events to facilitate its operations. So how does the archaeoastronomy of the fishing community in the Selayar Islands Regency fare according to astronomical analysis? They can predict the weather by looking at the stars that show at morning or Crux is located in the constellation Bintoeng Sapo Salayya. So Ursa major is bintoeng purung-purung. The following are the research's ramifications: 1) There are now few persons in the Selayar Islands Regency who are familiar with using constellations to predict the weather and discern the cardinal directions. The fishing population in the Selayar Islands Regency should thus be taught the custom of using cardinal directions and predicting the weather using constellations and the moon, say researchers.before dawn, which helps them decide when to go for work. Additionally, the phenomenon can offer a suggestion for figuring out the cardinal directions. Bintoeng purung-purung, bintoeng Pattaungang, bintoeng sapo salayya, bintoeng pikka-pikka, and bintoeng tallu are the constellations that are employed. What they truly saw was bintoeng tallu, or the constellation Orion, according to astronomy. 2) Because understanding of constellations is still necessary for forecasting weather and cardinal directions, researchers expect that the fishing community in the Selayar Islands Regency will keep up and preserve this tradition. It is undeniable that modern technology, despite its sophistication, is not always reliable, particularly when it comes to forecasting the weather for fishing areas and the cardinal directions.